Pengaruh Pembelajaran Kooperatif Teknik Dua Tinggal Dua Tamu (Two Stay Two Stray) terhadap Hasil Belajar IPS Terpadu Siswa Kelas VIII Semester Genap SMP N 19 Bandar Lampung - Zainal, Vetri Yanti (Lentera: Jurnal Ilmiah Kependidikan, 2016)
The purpose of this study was to determine the effect of the use of cooperative learning techniques two stay two guests (two stay two stray) to learning outcomes of integrated IPS second semester of eighth grade students of SMP Negeri 19 Bandar Lampung in academic year 2014/2015. The method used in this research is the experimental method.  Based on the hypothesis testing results obtained using thit thit = 7.66 and from 0.05 significance level distribution tables known ttab = t (1 - Â½a) = 2.02 and t (1-Î±) = 1.68. It can be concluded that the entire hypothesis proved to be true, which means that there is influence of using cooperative learning techniques two stay two guests (two stay two stray) on learning outcomes IPS Integrated second semester of eighth grade students of SMP Negeri 19 Bandar Lampung in academic year 2015/2016. The average results of social studies integrated students who use cooperative learning techniques two stay two guests (two stay two stray) higher than the results of social studies integrated students who do not use cooperative learning techniques two stay two guests (two stay two stray) against results Integrated social studies second semester of eighth grade students of SMPN 19 Bandar Lampung in academic year 2014/2015.